Herding behavior in the Egyptian stock market - Allam, Noha (AUC Knowledge Fountain, 2014)
This paper tests for the existence of herding behavior in the Egyptian stock market using daily and monthly data of listed companies on the Egyptian stock Exchange. We follow the methodology of Christie and Huang (1995) and Chang, Cheng, and Khorana (2000) to test for the presence of herding behavior in general, during up and down times (times of stress in the market), and during bearish and bullish market phases. We also split the sample into pre-revolution and post-revolution periods to test the effect of 25th January, 2011 revolution on herding behavior in the market. We found that: first, the Egyptian stock market exhibits herding behavior in general and weak adverse herding in stressful conditions; second, prolonged effects of adverse herding exist in up markets only and herding behavior is a short-lived phenomenon; third, no evidence of herding behavior during bull and bear markets was noticed; fourth, during the pre-revolution period, in pre-post revolution analysis, herding existed in the Egyptian stock market in general and weak adverse herding existed during times of market stress as well as during bullish market phases, however no evidence of herding behavior during bearish market phases was observed; fifth, interestingly, during post-revolution period, adverse herding exists in all market states; stressful conditions, in general, and during bullish and bearish phases; and finally, after modifying the model for multicollinearity and autocorrelation, no evidence of herding behavior in the Egyptian stock market in general for all tested periods was recorded.